Psychological Features of Self-Discipline Manifestation in Cadets - S S Kudinov; T V Andreyeva (Peoples' Friendship University of Russia (RUDN University), 2012)
The psychological aspect of manifestation of the cadets' self-discipline is analyzed in the frame of A.I. Krupnov's conceptual approach in this article. The research is focused on the comparative analysis of high and low levels of cadet's self-discipline.